2017
DOI: 10.1155/2017/7949361
|View full text |Cite
|
Sign up to set email alerts
|

Two Different Cell Populations Is an Important Clue for Diagnosis of Primary Cutaneous Adenoid Cystic Carcinoma: Immunohistochemical Study

Abstract: Primary cutaneous adenoid cystic carcinoma (PCACC) is a very rare malignancy. The differential diagnosis of PCACCs in pathology practice can be difficult and a group of primary and metastatic lesions, including adenoid basal cell carcinoma of the skin, should be considered in the differential diagnosis. Besides histomorphological clues, immunohistochemistry studies are very helpful in the differential diagnosis of PCACC. We report herein a case of PCACC with extensive immunohistochemical studies and review the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
0
18
0
1
Order By: Relevance
“…Immunohistochemically, Alkan BI et al reported in his case study that PCACC showed BerEp4, CEA, CD117(C-kit), and CK7 expression in the regions neighboring the luminal areas, and p63 and SMA positivity were detected in myoepithelial cells at the periphery of the cell islands. He said the two different cell populations provided an important clue for diagnosis because the tumor cells showed ductal and myoepithelial differentiation [5]. In fact, these features helped us for diagnosis in this case.…”
Section: Discussionmentioning
confidence: 89%
“…Immunohistochemically, Alkan BI et al reported in his case study that PCACC showed BerEp4, CEA, CD117(C-kit), and CK7 expression in the regions neighboring the luminal areas, and p63 and SMA positivity were detected in myoepithelial cells at the periphery of the cell islands. He said the two different cell populations provided an important clue for diagnosis because the tumor cells showed ductal and myoepithelial differentiation [5]. In fact, these features helped us for diagnosis in this case.…”
Section: Discussionmentioning
confidence: 89%
“…10 Histologically the tumor cells show epithelial and myoepithelial differentiation. 11 Morphologically PACC is indistinguishable from ACC of other sides and metastasis should be excluded clinically. 10 Compared to its salivary gland synonym, PCACC has an indolent course, but local recurrences and rare nodal or metastatic spread may occur.…”
Section: Discussionmentioning
confidence: 99%
“…2,13 Similarly, it has been shown that epithelial cells in ACC are stained with PanCK, CD117, CK7, and myoepithelial cells with p63 and calponin. 9,11,14 However, there are publications considering that β-catenin staining pattern can work in discrimination. Im et al detected nuclear β-catenin staining in 70% of ES cases.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…Immunohistochemistry is useful for the diagnosis of ACC ( 16 , 18 ). ACC is characterized by slow progression but has a high propensity to invade and metastasize, particularly via perineural invasion, which occurs in ≤70% of ACC cases ( 19 ). ACC involving the skull base (orbital contents/bone, sinonasal cavities, nasopharynx, cavernous sinus, clivus, pterygopalatine fossa and infratemporal fossa) is usually identified via novel imaging techniques ( 20 ).…”
Section: Discussionmentioning
confidence: 99%